Work organization in social enterprises: A source of job satisfaction? - Joutard, Xavier; Petrella, Francesca; Richez‐Battesti, Nadine (Kyklos, 2025)
Many studies suggest that employees of social enterprises experience greater job satisfaction than employees of for‐profit organizations, although their pay and employment contracts are usually less favorable. Based on linked employer–employee data from a French survey on employment characteristics and industrial relations and using a decomposition method developed by Gelbach (2016), this paper aims to explain this somewhat paradoxical result. Focusing on work organization variables, we show that the specific work organization of social enterprises explains a large part of the observed job satisfaction differential both in general and more specifically, in terms of satisfaction with access to training and working conditions. By detailing the components of work organization, the higher job satisfaction reported by employees in social enterprises stems from their greater autonomy and better access to information. In contrast to earlier studies, however, our results show that these work organization variables do not have more value for social enterprise employees than for for‐profit organization employees in the case of overall job satisfaction. This result casts doubt on the widespread hypothesis that social enterprise employees attach more weight to the nonmonetary advantages of their work than their counterparts in for‐profit organizations.